The Impact of Critical Life Points and Events for Survivors of Institutional Child Sexual Abuse: Understanding Trauma and the Role of Compensation in Recovery - Briggs, Lynne (Journal of interpersonal violence, 2023)
Although the impact of child sexual abuse (CSA) is well documented in the international literature, little is known about the critical points of recovery across the life course for survivors of institutional CSA. The aim of this study was to identify critical points, or events across the life course that may increase, or decrease, a survivor’s vulnerability to the complex traumatization of institutional CSA (ICSA). The sample consisted of two hundred and forty-eight witness statements extracted from the 56 publicly available case studies presented to the Australian Royal Commission into Institutional Responses to Child Sexual Abuse during 2013–2016 (Commonwealth of Australia, 2017). A content analysis and thematic coding of the statements identified seven main themes in the witness statements (Gender, Organization, Triggers, Trauma, Mental Health, Intervention and Compensation), that appeared to be critical events across the life course. The themes were transformed into variables for further analysis using SPSS. Significant Likelihood Ratios were found between associations with the organization where the abuse occurred and between triggers and breastfeeding/sensory, breast feeding/childcare, emotional and physical distress, and mental health (p < 0.01). Significant associations were also found between receiving compensation for the CSA and triggers, trauma, breast feeding-sensory and childcare (p < 0.05) and gender and breast feeding (p < 0.05). Overall, the findings showed that triggers can be random across the life course occurring mainly through indirect association, or in situations that evoke memories of the CSA, and that receiving compensation can assist survivors in their recovery journey. The findings also indicate the need for health care professionals to be aware of the critical points in a CSA survivor’s recovery and how triggers may impact on their mental welling throughout the life course.